Demonstrators’ slogans in Tahrir square (Analytical study of the communication message) - الشجيري سهام (ALBAHITH ALALAMI, 2014)
The research entitled "The Slogans of Demonstrators at Al-Tahreer Square – analytical study for communicative letters" studies the slogans of demonstrators as a communicative means having many signs reflecting the political, social, cultural relations exist in the minds of people. It is so easy to understand its meaning, examining its goals; and explaining their meanings. For these reasons, we have chosen such a topic. Since the means of communications transfer letters between a sender and receiver, the importance of this research is that it is a researchable trial to acknowledge the issues behind the demonstrators’ slogans and the different styles have been chosen by them for a whole year; the different sides of the demonstration since it is a theoretical and scientific problem d and discussed. So, it is so important to focus on the content and issues of these slogans whether they are a signboard, shouting or songs. The research concludes that the demonstrators have used different methods to express their viewpoints; the slogans shows the huge variety in the media speech tools; the different cultural backgrounds of the demonstrators as well as their needs. Also, the slogans show the needs of people to live in a better economic and social life in Iraq.